Balanced Cultural Identities Promote Cognitive Flexibility among Immigrant Children - Spiegler, Olivia; Leyendecker, Birgit (Frontiers in Psychology, 2017)
The acculturation complexity model suggests that immersion into dissonant cultures promotes cognitive skills in biculturals (Tadmor & Tetlock, 2006). In the present study, we examined links between identity acculturation and executive functioning. Turkish-German immigrant origin children (N = 225; M = 11 years, SD = 1.6 years, 99 males) were given questions about their identification with Turks and Germans to capture bicultural involvement and a Dot Task (using Hearts and Flowers) to measure executive functioning. Results showed that Turkish-German bicultural children who endorse both cultures with equal strength did not have a cognitive advantage in working memory and inhibition compared to their peers who more clearly preferred one culture over the other. However, bicultural children who endorse both cultures with equal strength performed significantly better on a switching task that required cognitive flexibility. The study highlights the potential cognitive benefits associated with biculturalism.